Safety and long-term efficacy of hybrid-argon plasma coagulation for the treatment of Barrett's esophagus: An Australian pilot study (with video) - Dominic Andre Staudenmann; Ellie Patricia Skacel; Tatiana Tsoutsman; Arthur John Kaffes; Payal Saxena (Society of Gastrointestinal Intervention, 2021)
Background : : Five to ten percent of all patients undergoing radiofrequency ablation (RFA), which is the most established technique for Barrett's esophagus (BE) ablation-develop strictures. Hybrid-argon plasma coagulation (APC) combines APC with submucosal saline injection that was recently developed to tackle this problem. The aims of this pilot study were to evaluate the feasibility, tolerance, safety and long-term efficacy of hybrid-APC for the treatment of BE. Methods : : Patients with histological proven BE were selected for hybrid-APC. Prior to APC thermal ablation the mucosa was lifted using a submucosal high-pressure water jet injection system (Erbejet 2; Erbe, Tuebingen, Germany). Short-term (< 48 hours) and long-term (> 48 hours) safety were evaluated. Efficacy of ablation was measured at 3, 6, 12 and 24 months at follow-up endoscopy by evidence of macroscopically complete resolution of BE mucosa and/or histologically complete resolution of intestinal metaplasia (CRIM). Results : : Eleven patients were included in the study (average age, 68.2 years; male 72.7%). Eight patients (72.7%) were treatment naive, 9.1% (n = 1) had prior RFA and 18.2% (n = 2) had prior endoscopic mucosal resection. Two patients were excluded from the study. Nine patients (100%) had macroscopic remission and 88.9% (n = 8) had macroscopic remission and microscopic CRIM at 24 months after hybrid-APC ablation. No treatment-related stricture or other major complications were observed, 1 patient (11.1%) reported minor adverse effects. Conclusion : : In this prospective pilot study, hybrid-APC appears safe, feasible and effective after 24 months, which has not been evaluated so far. Further large, multi-centre trials are warranted to confirm the present results.